2017
DOI: 10.1097/iae.0000000000001364
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Hypertension After Intravitreal Dexamethasone (Ozurdex) Sustained-Release Implant

Abstract: Purpose To evaluate ocular hypertension (OHT) after Ozurdex injection to determine the incidence of OHT, therapy of OHT, and any associative factors such as diagnosis, underlying glaucoma and therapy, or sequential Ozurdex injection(s). Methods Retrospective consecutive case series with patients receiving one or more intravitreal Ozurdex implantations at a tertiary care academic center. OHT was defined as a single measurement of ≥30 mmHg, or an increase of ≥10 mmHg from baseline. Results Ninety-four inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
5
27
0
2
Order By: Relevance
“…e percentage of transient increase in IOP (29.1%) was similar to that reported in the previous studies [6,17,20,21]. Similarly, the surgery for glaucoma has been previously described after single or multiple Ozurdex injections [21,22]. In our affected patient, the ocular hypertension completely and stably regressed after trabeculectomy, and considering the entire FU period of 43 months, intravitreal injections still resulted in a consistent improvement in visual acuity, suggesting that the treatment was beneficial despite the adverse event.…”
Section: Discussionsupporting
confidence: 87%
“…e percentage of transient increase in IOP (29.1%) was similar to that reported in the previous studies [6,17,20,21]. Similarly, the surgery for glaucoma has been previously described after single or multiple Ozurdex injections [21,22]. In our affected patient, the ocular hypertension completely and stably regressed after trabeculectomy, and considering the entire FU period of 43 months, intravitreal injections still resulted in a consistent improvement in visual acuity, suggesting that the treatment was beneficial despite the adverse event.…”
Section: Discussionsupporting
confidence: 87%
“…The Geneva study group’s (2011) results showed that a maximum rise of IOP was observed within 60 days of implantation in patients with ME due to BRVO [ 1 ]. Similarly, Chin et al [ 26 ] have reported that the greatest IOP elevation was seen at the 1.5-month to 2.5-month follow-up interval. A study into IOP elevation with intravitreal DEX implantation in the real world reported that the cumulative probability of having an IOP ≥ 21 mmHg was 20% at 1–2 weeks, and the probability of having an IOP ≥ 25 mmHg or ≥35 mmHg was 5% and 2% at 1–2 weeks, respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the safety of DEX was also guaranteed, without significant IOP elevation in the whole study group, a result which has been suggested as a possibility in previous studies. [ 12 , 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] DEX can be controlled-released from the device within 6 months, with gradual delivery of medication after the polymer device undergoes hydrolysis in the vitreous cavity. [ 11 , 12 ] Currently, DEX is used to manage the ME induced by branch retinal venous occlusion, central retinal venous occlusion, posterior uveitis and diabetic macular edema. [ 11 , 13 ] It shows similar effectiveness compared to anti-angiogenic agents but with less frequent injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation